Uji Aktivitas Analgetik Ekstrak Etanol Daun Inggu (Ruta angustifolia [l.] Pers) Pada Tikus Putih Jantan - Yane Dila Keswara; Sri Rejeki Handayani (Journal Syifa Sciences and Clinical Research, 2019)
Pain is an uncomfortable feeling caused by strong or destructive stimulation, if unchecked can affect daily routine. This study aims to determine the analgesic effect and dosage of the leaf extract ethanol, as well as to determine the effectiveness of the leaf extract ethanol as a narcotic analgesic by the Tail Flick method or as a non-narcotic analgesic by the Paw Pressure Test Randall Selitto method. Extraction was done by maceration of leaf powder with a solvent 96% ethanol. 25 male Wistar white rats were divided into 5 groups, positive group mefenamic acid 9 mg /200 g BW for the Paw Pressure Test Randall Selitto Method and tramadol 0.9 mg /200 g BW for the Tail Flick Method, negative control CMC Na 0,5%, ethanol extract leaves inggu leaves a dose of 10 mg /200 g BW, 20 mg /200 g BW and 40 mg /200 g BW. The data obtained were analyzed by ANOVA test, then LSD test was used to determine differences between groups. The results showed extract dosage of 10 mg /200 g BW, 20 mg /200 g BW, 40 mg /200 g BW had analgesic effect. Extract dosage of 20 mg /200 g BW and 40 mg /200 g BW in the Randall selitto Paw Pressure Test method is equivalent to mefenamic acid, extract dose 10 mg /200 g BW, 20 mg /200 g BW, and 40 mg /200 g BW the Tail Flick method is equivalent to Tramadol. Ethanol leaf extract is more effective as a narcotic analgesic by the Tail Flick method.